Geochemical characterization of the geothermal system at Villarrica volcano, Southern Chile; Part 1: Impacts of lithology on the geothermal reservoir. (July 2018) - Held, S.; Schill, E.; Schneider, J.; Nitschke, F.; Morata, D.; Neumann, T.; Kohl, T.
Highlights: Lithological control on geothermal circulation pattern. Chlorofluorocarbons for mixing analysis. Fault controlled geothermal system. Medium enthalpy geothermal system at active volcano. Abstract: Besides temperature, mineralogy, residence time and dilution are crucial for assessing water-rock interaction intensity. The geothermal system at the Villarrica-Quetrupillán-Lanín volcanic chain, Southern Chile, is located across a prominent lithological transition from plutonic rocks of the North Patagonian Batholith (NPB) to volcano-sedimentary units. With the goal to investigate the impact of lithology on medium-enthalpy geothermal fluids, 15 hot spring discharges were sampled and analyzed for anthropogenic tracers and isotopic composition and compared to the analyses of 31 reservoir rock analogues. Comparison of strontium isotope signatures between rock analogues and hot spring discharges allow an allocation of associated reservoir rocks. Chlorofluorocarbons quantify the dilution of the geothermal springs by shallow groundwater, ranging from almost CFC-free samples to dilution with modern meteoric water by up to 50 %. Fluids discharging from plutonic rocks have low proportions of dilution with modern waters, while hot springs discharging from the volcano-sedimentary rocks have a higher and variable dilution with modern waters. The fractionation of oxygen isotopes of the SO4 -H2 O system reveals reservoir temperature estimates of 80–100 °C in the plutonic sequence matching discharge temperatures. For the springs discharging from volcano-sedimentary units higher reservoir temperatures of 100–140 °C are calculated. On basis of the analysis, a conceptual reservoir model can be derived. Fast fluid ascent is indicated along Liquiñe-Ofqui fault system in the NPB by similar discharge and reservoir temperatures and low surficial dilution rates. Large differences in discharge and reservoir temperatures in the Cura-Mallín formation along with a high influx of surficial water may be attributed to a more branched pathway pattern. In conclusion lithology maybe an important factor when coming to the utilisation of geothermal resources.